Incidence of Gatroenteritis Induced Acute Renal Failure and its Associated Risk Factors - Nabiha Rizvi, Iqra Iftikhar, Ali Abbas, Mehrin Farooq, Syed Khurram Shehzad Kazmi, Waseem Amir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To record the incidence of AKI following acute gastroenteritis and to poor prognostic factors in patients having AKI following gastroenteritis. Methodology: We enrolled 92 cases with above 14 years of age diagnosed to have acute kidnay injury due to gastroenteritis. Detailed history, clinical examination and laboratory investigations were done at admission. Serum creatinine, urea, potassium were done daily. Other investigations done were liver function tests, urine complete examination, serum sodium levels, ultrasound abdomen and renal failure and its associated factors were recorded. Results: We studied 92 patients admitted to our hospital with acute gastroenteritis. Among those 48(54%) patients had AKI whereas 44(46%) patients didn’t developed AKI following acute gastroenteritis. AKI was more common in males(72%) as compared to females(28%). The most common manifestation was oliguria and anuria in( 66%)of the cases, (43%) of the patients having AKI had hypertension and (29%) had DM.(94%) patients were managed conservatively and (6%) required hemodialysis. Conclusion: We concluded that AKI is highly prevalent in patients with gastroenteritis whereas diarrhea is a major risk factor of AKI. Keywords: Gastroenteritis, Acute renal failure(AKI), risk factor